Occurrence and Epidemics of Bacterial Canker of Kiwifruit in Korea - Kim, Gyoung Hee (Plant Pathol J, 2017)
Bacterial canker is the largest limiting factor in the cultivation and production of kiwifruit worldwide. Typical symptoms comprise necrotic spots on leaves, canker and dieback on canes and trunks, twig wilting, and blossom necrosis. Pseudomonas syringae pv. actinidiae (Psa), which is the causal agent of kiwifruit bacterial canker, is divided into four biovars based on multilocus sequence analysis of different genes, additional PCR testing of pathogenic genes (argKtox cluster, cfl, and various effector genes), and biochemical and physiological characterization. Bacterial canker caused by Psa biovar 2 designated Psa2 was detected for the first time on the green-fleshed kiwifruit cultivar Hayward in 1988 and the yellow-fleshed kiwifruit cultivar Hort16A in 2006 in Korea. Psa biovar 3 designated Psa3, responsible for the current global pandemics of kiwifruit bacterial canker, began to appear in Korea in 2011 and caused tremendous economic losses by destroying many vines or orchards of yellow-fleshed kiwifruit cultivars in one or several growing seasons. Bacterial canker epidemics caused by both Psa2 and Psa3 are prevalent in Korea in recent years. In this review, we summarize the symptomatology, etiology, disease cycle, diagnosis, and epidemiology of kiwifruit bacterial canker in Korea.